GLUTEN-SENSITIVE ENTEROPATHY IN CHILDREN: STATE OF THE PROBLEM ON MODERN STAGE - А.А. Horobets (Bogomolets National Medical University, 2015)
The article is dedicated to problems of gluten-sensitive enteropathy (celiac disease) appearing nowadays on modern stage of pediatric science development. In particular, special attention is paid on the rate of non-diagnosed cases of the disease, the problem of violation of gluten-free diet by children with following reflection of this phenomenon and the problem of celiac diseases diagnosing several months and, sometimes, years after gluten-free diet prescription which complicates diagnostics and makes it impossible in some cases. Gluten related disorders - the problem which is being actively investigated and discussed by scientists world wide - is described in the article as well. Such gluten related disorders as gluten sensitivity without celiac disease and food allergy to cereals' proteins are discussed and differentiated with celiac disease. The problem of celiac disease accompanied by concomitant pathologies, especially exocrine insufficiency of the pancreas, is pointed out besides. It is discussed to be one of prior directions of gluten-sensitive enteropathy problem following study.